Who's afraid of tax competition? Harmless tax competition from the new European Member States - Lahrèche-Révil, Amina (Paris, 2006)
"This paper investigates the tax sensitivity of foreign direct investment (FDI) in the context of EU enlargement to Eastern European countries. Using two alternative specifications of a gravity equation, it shows that the E25 is heterogeneous as far as FDI location determinants are concerned. However, the results are at odds with usual consensus:while tax differentials do impact on FDI in the EU15, they are shown to have had no impact on the new member states during the period of analysis (1990-2002). Similarly, other factors such as unit labor costs and price-competitiveness fail to explain FDI inflows to the new EU member states. Simulation exercises run on statutory taxation attend to assess empirically the impact of various tax convergence scenarios. They are shown to imply limited changes in FDI inflows, on the basis of FDI flows and tax differentials observed in 2002."